1975
DOI: 10.2134/agronj1975.00021962006700060002x
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response to Soil Warming: Vegetable Crops1

Abstract: Waste heat appears in the form of warm condenser cooling water from power generating plants. It has been proposed to use this water with temperatures ranging from 25 to 40 C for warming soils by pumping it through buried pipes. Experiments were conducted to determine the effect of warming soils in this manner on the growth rates and yields of several crops. The proposed system was simulated with electrical heating cables buried 92 cm deep at a spacing of 183 cm. Heat source temperatures ranged from 35 to 38 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
2
9
1
1
Order By: Relevance
“…For leaf biomass specifically, the presence of root‐zone heating increased shoot fresh weight in both years, an outcome consistent with previous reports 36, 41, 42. However, the effect was greatest in 2009 and corresponded to the potential impact of soil heating given ambient temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…For leaf biomass specifically, the presence of root‐zone heating increased shoot fresh weight in both years, an outcome consistent with previous reports 36, 41, 42. However, the effect was greatest in 2009 and corresponded to the potential impact of soil heating given ambient temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…The influence of air-or water-mediated active root-zone heating is most often studied in growth chambers or greenhouses (Economakis, 1997;Elwell et al, 1985;Li et al, 1994;Shedlosky and White, 1987). Fewer recent studies (Bumgarner et al, 2012;Hunter et al, 2010) have capitalized on earlier reports (e.g., Cameron Brown and Gray, 1957;Canham, 1952;Rykbost et al, 1975) and considered the impacts of direct soil heating in differently engineered low-and high-tunnel systems, especially in temperate climates.…”
Section: Microclimate Effects On Plant Biomassmentioning
confidence: 99%
“…The use of heating cables significantly increased soil temperature in all trials but had its greatest effect when temperatures were lowest late in the Fall and early in the Winter. Others have also reported that heating cables increase soil temperature (Bumgarner et al, 2011(Bumgarner et al, , 2012Hunter, 2010;Rykbost et al, 1975). Heating cables allowed spinach roots to be exposed to soil temperatures within 7 to 23°C range which are optimal for spinach root growth.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of soil heating cables generally leads to an increase in the total yield for early spring grown tomatoes, bush beans, peppers, broccoli, and lettuce (Bumgarner et al, 2011;Hunter et al, 2012;Rykbost et al, 1975) and results in increased yield for winter-grown lettuce (Bumgarner et al, 2011(Bumgarner et al, , 2012Hunter, 2010). Additional heat increased total plant biomass and nutrient uptake by maintaining root zone temperatures above freezing and closer to optimal root temperature.…”
mentioning
confidence: 99%